Three-dimensional simulations of isobaric premixed flames freely propagating in narrow circular channels: breaking of symmetry. Issue 7 (10th November 2021) - Dejoan, Anne; Kurdyumov, Vadim
Abstract : In this work we perform three-dimensional simulations to study the breaking of symmetry of lean premixed isobaric flames propagating in narrow channels of circular cross-section subject to an inlet Poiseuille flow. In particular we consider the effects of the flow rate, the channel diameter, wall heat-losses for flames with the Lewis number ( Le ) equal or less than unity. Numerical analysis shows that, for Le  = 1 and under adiabatic conditions, a supercritical bifurcation occurs at flow rates exceeding a critical value and the axisymmetric flame becomes unstable, giving rise to a non-axisymmetric flame. For flames with Le <1, a subcritical bifurcation occurs and we report multiplicity of stable solutions: the flame can be axisymmetric and non-axisymmetric for the same values of parameters. It is important to underline that both types of solutions are stable, and thus can be observed experimentally. In the presence of wall heat-losses, the critical flow rate corresponding to the bifurcation point increases. This indicates a promoting effect of wall heat-losses on flame shape symmetry. We also find that an extinction gap can appear when increasing the flow rate. For the smaller Lewis number ( Le  = 0.5) we observe a complex flame dynamics, showing the coexistence of steady and oscillatory combustion regimes.